2017
DOI: 10.18520/cs/v113/i07/1327-1336
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment, Physical Activity and Diabetes

Abstract: Type-2 diabetes, which has emerged as a global epidemic in recent years, is strongly related to lifestyle and economic change. The built environment (BE) influences lifestyle factors such as physical activity and diet. Evidence shows that individuals who live in neighbourhoods with the availability of destinations for physical activity within walking/cycling distance are more likely to engage in the same and thereby improve their health. Walking can be increased in neighbourhoods by providing useable and unenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The effects of walking in neighbourhoods can be increased by providing pedestrian paths that are usable and unobstructed, by implementing motor-traffic reduction strategies, by increasing good street connectivity and by providing parks, green space, playgrounds and recreation areas. 65 Our systematic review found consistent evidence of an association of the food environment with T2D risk/ prevalence. An increase in fruit and vegetable vendor availability was associated with a lower T2D risk in an Indian study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The effects of walking in neighbourhoods can be increased by providing pedestrian paths that are usable and unobstructed, by implementing motor-traffic reduction strategies, by increasing good street connectivity and by providing parks, green space, playgrounds and recreation areas. 65 Our systematic review found consistent evidence of an association of the food environment with T2D risk/ prevalence. An increase in fruit and vegetable vendor availability was associated with a lower T2D risk in an Indian study.…”
Section: Discussionsupporting
confidence: 62%
“…The effects of walking in neighbourhoods can be increased by providing pedestrian paths that are usable and unobstructed, by implementing motor-traffic reduction strategies, by increasing good street connectivity and by providing parks, green space, playgrounds and recreation areas. 65 …”
Section: Discussionmentioning
confidence: 99%
“…least partially be due to regional differences in physical activity and dietary patterns. 29,30 Employment patterns may be a potential explanation for this, as there are substantial differences in occupations between people living in urban vs rural areas. 31 These differences may also be due to differences in sociodemographic characteristics of participants treated in rural areas, compared with those who are not treated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have constructed quantitative indicators of green space (e.g., green space rate, quantity and quality of green space, accessibility of green space) to quantify the correlation with the prevalence of CVD. To do this, studies have reported the influence of various elements of green space on cardiovascular health, such as a negative correlation between green space rate, quantity, and accessibility of green space and the prevalence of CVD with a radius of 1-3 km [18,[75][76][77][78][79][80]. In addition, the youth is a group that was identified as needing special attention.…”
Section: Cluster Analysis Of the Literature Co-citation Networkmentioning
confidence: 99%